BEBERAPA CATATAN TENTANG EBONI DI SULAWESI - Wesman Endom (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Central Sulawesi is one of the areas where Eboni species (Ebony spp) grows naturally. The other areas are North Sulawesi and North Maluku. The species have valuable wood and many people like them due to their artistic and black appearance.In the last few years, the species heve been decreasing and today they can be categorized as endangered or at least as in. vulnerable codition. Since 1988, in accordance to the Ministry of Forestry Decision No 988/Menhut-IV/1988, the harvesting of Eboni had been banned.The observation of the logged forest area shows that the number of Ebony trees in the field is very small. To protect the species from their extinction, the strict regulations are required and the activities of the planting and tending need to be intensifed.The other observation result are as follows :1. Most felling activity had been carried out on the small diameter of 35 cm while the trees are still growing well to reach larger diameter (60 cm or more).2. Part of the wood utilized was only heartwood that had the volume of about 42% ot total volume. Therefore, to have larger volume, is better to harvest only big trees of diameter 60 cm or more.3. THe clear bole of the trees of diameter 35 cm is ranging from 10-15 m long.4. Futher research on the increment, harvesting cycle and Silviculture techniques be conducted in order to manage the species sustainably.